Estudo e cadastro de áreas de risco de inundação na área urbana do município de Restinga Sêca - RS - Freitas, Rafael Bilhan (2017)
Occupying areas naturally prone to adverse events, such as floods, may have negative impacts on the economy and social problems for the affected population. This is a problem of the municipality of Restinga Sêca located in the central region of the State of Rio Grande do Sul, where the floods are recurrent. The general objective of this research consisted in the elaboration of a cadastre of the properties in the areas with risk of flood in the urban area of the municipality, that occur in the Sanga da Restinga creek (located at West of the urban area) tributary of the Vacacaí-mirim river. To achieve this objective, studies were carried out on the flood history between 1980 and 2016, as well as surveys of areas of susceptibility, registration of elements exposed to flood hazard, vulnerability and risk of flood. The methodological procedures involved the bibliographic review of the subject matter, organization of the cartographic base, obtaining information about the study area, inventory of events and registration, definition of areas susceptible to floods, flood hazard analysis, vulnerability study of Affected population and determination of flood risk areas. The materials used in this research were satellite images, topographic maps, GPS devices and the registry base of the city of Restinga Sêca, with level curves with 1 meter equidistance. The cartographic products were generated by means of geoprocessing techniques in a Geographic Information System (GIS) environment. The results indicate that during the analyzed historical series 14 flood events were recorded. The susceptibility shows that about 10% of the urban perimeter of the municipality is in an area prone to flood occurrence. The areas with the highest number of elements exposed to danger, vulnerability and risk are associated with the Sanga da Restinga flood and are located mainly southwest of the urban area of Restinga Sêca. The use of the information produced in this research can be of great importance for the decision making related to disaster prevention and mitigation, planning and territorial planning policies and flood risk management in the municipality of Restinga Sêca.